Analisis Proksimat Bronok (Acaudina Malpadioides) - Yunisa Yunisa; Suhaera Suhaera; Shinta Sari (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Karimun Regency, Riau Archipelago Province has an ocean with abundant marine life and has not been used optimally. Bronok (Acaudina malpadioides) is a type of marine biota that lives in muddy coastal areas. Bronok on Karimun Island is consumed fresh and is believed to reduce joint pain. This study aims to determine the content of water, ash, fat, protein and carbohydrates in bronok (Acaudina malpadioides). The proximate analysis includes the water content test using the thermogravimetric method, the ash content using the dry ashing method, the fat content method (Soxhlet), the protein content method (Kjeldhal), and the carbohydrate content method (By different). Bronok that has been analysed for proximate content is found to be present at 16% water content, 29,2% ash content, 5,39% fat content, 11,25% protein content and 38,16% carbohydrate content.